#TITLE_ALTERNATIVE# - MANOTAR ARITONANG (NIM 12204048), TUAN
Determining the value of OGIP (Original Gas In Place) of a gas reservoir is an important thing to be done. Determining the value of OGIP can be done before or after a gas field has been produced. One of the method that used to determine the value of OGIP in gas reservoir after the field begin for producing is P/z method. However, this method is limited to reservoir which its driving mechanism is depletion drive (volumetric reservoir). Reservoir that have water drive mechanism in it will give a wrong result of OGIP by using this method. Solution Plot method is one of the methods that can be used to look if there is water drive mechanism in a reservoir gas. By knowing the type of driving mechanism in the reservoir so determining the value of OGIP become more accurate. This paper will discuss the used of this solution plot for predicting if there is a water drive mechanism system in a reservoir gas in early time after production start. By thus, the mistaken that have been done to determine the value of OGIP can be corrected immediately. The effect of the size of the reservoir, pressure and gas production rate to the solution plot also will be discussed in this paper. The information about the kind of driving mechanism system of a reservoir gas will be useful for decision making during production time, like the design of surface production facilities and economic policies of a reservoir gas.